Diachronic Toponomastics and Etymology: Epistemological Proposals According to the New Convergence Theory - Perono Cacciafoco, Francesco (2016)
This paper introduces the basic principles of the New Convergence Theory (NCT) in the field of Indo-European Linguistics. The first part is inherent in a brief evaluation of the current approaches to Indo-European origins and Etymology and in the theoretical explanation of the NCT’s epistemological fundamentals, the second part deals with some examples of etymological reconstructions conducted according to this innovative approach in which Historical Phonetics, historical Semantics, historical Geography, and Landscape Archaeology participate in recovering the most ancient origins (or ‘proto-origins’) of names (‘paleo-names’) and of languages in prehistoric Europe.